Implementation Of Technology Towards The Merdeka Curricullum Doing Diagnostic Assessment For Student with Autism Spectrum Disorder In Preschool Level - Suryadi, Yeanny; Yus, Anita; Milfayetti, Sri (Politeknik Ganesha Medan, 2024)
This research aims to developing an effective and applicable diagnostic assessment instrument that has been prepared based on the requirements of competency standards for graduates at the preschool institute. The instrument functions is to separate mild and moderate levels of the autism spectrum, for students with learning disabilities resembling autism spectrum symptoms in early childhood. This research used R and D methode from Borg and Gall with result is this application product containing a 23-item questionnaires that has been validated by material, language and media experts. Subject of this research is teachers of preschool institutions, and the objek is the instrument of diagnostic assessment wich researcher build. The practicality test results of this instrument have a percentage level of 92.52% in the 'very practical' category, with a validity test level of 84%, on the Likert scale showing the instrument is 'very feasible'.